CO2-tolerant ceramic membrane driven by electrical current for oxygen production at intermediate temperatures - Zhang, K.; Meng, B.; Tan, X.; Liu, Lihong; Wang, Shaobin; Liu, Shaomin (Wiley-Blackwell Publishing, Inc., 2014)
In this work, an electrochemical oxygen pump ceramic membrane based on Sm0.2Ce0.8O1.9 (SDC) electrolyte and La0.6Sr0.4FeO3−δ (LSF) electrode was prepared and characterized by XRD, SEM, and EDX. The area specific resistance of the membranes was measured by impedance spectroscopy. The oxygen electrical permeation behavior of SDC/LSF membrane was investigated under different operating conditions. In consistent with the theoretical prediction from Faraday law, the oxygen flux value observed is closely correlated in quantity with the applied current density. The permeation (or Faraday) efficiency of SDC/LSF membrane could reach above 95% at lower temperatures (600°C–700°C). At 700°C, the oxygen flux through SDC/LSF membrane with 3000 mA/cm2 current density could reach ~9.97 mL/cm2/min. In addition, the prepared SDC/LSF membrane electrical performance was also tested under the presence of CO2. It was found that SDC/LSF membrane has excellent structure and permeation stability against CO2 gas, reflecting its potential applications like oxyfuel technologies and hydrocarbon oxidations.